``Namanya juga Pesantren'': A Photovoice Study about Self-adjustment of Students in Islamic Boarding School - Putri Rusli, Nurul Inayah; Wulan Saptandari, Edilburga (KnE Social Sciences, 2024)
Pondok Pesantren (PP) or Islamic boarding school is a popular religious educational institution in Indonesia. The characteristic of PP required students to live in a boarding school, this encouraged students to be able to adapt to the differences and limitations of PP. This study aims to find out how students adapt to PP. The participants are four female students in grade 2 of a PP junior high school in the city of Ternate, North Maluku. The method used in this study is photovoice and analyzed using thematic analysis with Nvivo 12 Pro software. Four themes of adjustment emerged from the findings are as follows: new habits, religious habits, facing and resolving challenges, and relationships. Keywords: adjustment, Islamic boarding school, photovoice